Transparency, health equity, and strategies in state-based protocols for remdesivir allocation and use. - Zippora Kiptanui (Public Library of Science (PLoS), 2021)
Background The Emergency Use Authorization (EUA) of remdesivir for coronavirus disease 2019 raised questions on transparency of applied strategy, and how to equitably allocate and prioritize eligible patients given limited supply of the medication. The absence of federal oversight highlighted the critical role by states in health policymaking during a pandemic. Objective To identify public state-based protocols for remdesivir allocation and clinical guidance for prioritizing remdesivir use and assess approaches and inclusion of language promoting equitable access or mitigating health disparities. Methods We identified remdesivir allocation strategies and clinical use guidelines for all 50 states in the U.S. and the District of Columbia accessible on state health department websites or via internet searches. Public protocols dated between May 1, 2020 and September 30, 2020 were included in the study. We reviewed strategies for allocation and clinical use, including whether protocols contained explicit language on equitable access to remdesivir or mitigating health disparities. Results A total of 38 states had a remdesivir allocation strategy, with 33 states (87%) making these public. States used diverse allocation strategies, and only 10 (30%) of the 33 states included language on equitable allocation. A total of 30 states had remdesivir clinical use guidelines, where all were publicly accessible. All guidelines referenced recommendations by federal agencies but varied in their presentation format. Of the 30 states, 12 (40%) had guidelines that included language on equitable use. Neither an allocation strategy or clinical use guideline were identified (public or non-public) for 10 states and the District of Columbia during the study period. Conclusions The experience with the remdesivir EUA presents an opportunity for federal and state governments to develop transparent protocols promoting fair and equal access to treatments for future pandemics.